The Effect of Glutathione Foliar Spray on Mitigating Salinity Stress Damage in Tissue-Cultured Date Palm (Phoenix dactylifera L.) Seedlings of Barhi Cultivar - Alarab, Emad H.A.; Suhaim, Aqeel A. (Basrah Journal Of Date Palm Research, 2024)
The experiment was conducted on two-year-old tissue-cultured date palm (Phoenix dactylifera L.) seedlings of the Barhi cultivar grown in pots to study the role of foliar glutathione application in mitigating salinity stress damage. Different concentrations of glutathione (0, 100, 200, and 300 mg L⁻¹) were applied as foliar sprays to the leaves of seedlings irrigated with two types of water: tap water (0.23 dS m⁻¹) and saline water with an electrical conductivity of 6.25 dS m⁻¹. The results showed that increased salinity levels led to a reduction in total chlorophyll content, along with significant increases in proline concentration and total soluble carbohydrate content. Additionally, saline water irrigation caused a significant increase in hydrogen peroxide (H₂O₂) and malondialdehyde (MDA) concentrations, coupled with a reduction in the membrane stability index compared to plants irrigated with low-salinity water. However, treating the date palm seedlings with different concentrations of glutathione resulted in an increase in total chlorophyll content and a noticeable reduction in proline, total soluble carbohydrates, hydrogen peroxide, and MDA levels, as well as an improvement in membrane stability in salinity-stressed plants.